Inducible clindamycin resistance among clinically significant staphylococcus aureus isolates in a tertiary care centre - NISHA SADANANDAN (Tropical Journal of Pathology and Microbiology, 2024)
INDUCIBLE CLINDAMYCIN RESISTANCE AMONG CLINICALLY SIGNIFICANT STAPHYLOCOCCUS AUREUS ISOLATES IN A TERTIARY CARE CENTRE                                         ABSTRACTObjective Staphylococcus aureus isolates with inducible clindamycin resistance may lead to  therapeutic failure on treating with Clindamycin. Aim:To detect inducible clindamycin resistance of clinically significant Staphylococcus aureus  isolates and MIC of clindamycin in them.Study designCrossectional studyStudy subjectsThe study was conducted in 200 clinically significant Staphylococcus aureus isolates from Govt medical college, Thrissur Kerala, India  over a period of one yearStudy methodsD test was done and  iMLSB, cMLSB, MS phenotypes were identified. Epsilometer test was done for determining the MIC of Clindamycin.. Statistical analysis was done using IBM statistical package for social sciences version 25(SPSS).Results Of the total  200 samples 132(66%) were MSSA and 68(34%) were MRSA.MS phenotypes 60(30%), iMLSB phenotype 53(26.5%),cMLSB phenotype 44 (22%), Erythromycin and Clindamycin sensitive strains 41(20.5%) and resistant strains 2 (1%). Inducible and constitutive resistance to clindamycin were more in MRSA.92% of iMLSB phenotypes  and 96% of MS phenotypes had MIC < 0.5(sensitive). 8% iMLSB phenotypes and 96% of cMLSB phenotypes had MIC >4(resistant). One isolate with  cMLSB phenotype  had MIC in intermediate range .ConclusionPrevalence of inducible clindamycin resistance in our hospital is high and more common among MRSA. E test helped to determine MIC in intermediate range (shown by  cMLSB phenotype )which is not possible by doing disc diffusion method alone.  Most common phenotype isolated was MS phenotype.KeywordsiMLSB, cMLSB, MS Phenotype, D test, MRSA, MSSA, MIC